HEAD INJURIES FROM ROAD TRAFFIC ACCIDENTS: OUTCOME IN THOSE WHO COULD NOT AFFORD COMPUTERIZED TOMOGRAPHY SCAN OF THE BRAIN - Mathias Nnanna Nnadi; Olufemi Babatola Bankole (Medico Research Chronicles, 1970)
Background Due to limited resources some of our patients who had head injuries could not afford the cost of computerized tomography (CT) scan of the brain. Our center covers many rural areas populated by peasant farmers and petty traders. Many of them do not have the financial capacity to pay for CT scan. We tried to see what the functional outcome among these poor patients would look like using road traffic accident as an etiological prototype. Objectives To find out the functional outcome of patients who had head injuries from road traffic accident but could not afford brain CT scan.Methods: It was a prospective study of patients who had head injuries from road traffic accident but could not afford CT scan of the brain. The study was carried out from 1st January 2011 to 31st December 2017. Patients were resuscitated in accident and emergency using advanced trauma life support protocols. Patients were admitted into the wards and managed till discharged. Data were collected using structured proforma and analyzed with Environmental Performance Index (EPI) info 7 software.Results: There were 155 patients. Males were 122. The age ranged from seven months to 75 years. The favorable functional outcome was 88.38%, while mortality was 11.61%. The outcome was affected by age and severity of injuryConclusion: The outcome in these patients was good. It was affected by injury severity and age.